Reforming English language teaching through the Merdeka curriculum: A case study on policy, pedagogy, and practice - Wiranegara, Dian Arsitades; Badriyah, Ima Mutholliatil; Jayanti, Septia Dwi (Journal of English Language Teaching and Learning (JETLE), 2025)
This study explored the implementation of Merdeka Curriculum in English language learning at the senior high school level in Indonesia. The objective was to examine the policy, pedagogical practices, and challenges when implementing this curriculum. As a qualitative case study, it employed purposive sampling involving English teachers, school principals, and students from a senior high school in East Jaya, Indonesia. The instruments used were semi-structured interview, classroom observation and focus group discussion. Thematic analysis was conducted to identify the patterns and themes related to curriculum implementation and its impact. The results showed that the Merdeka Curriculum is supported by policies that encourage student independence, student-centeredness, and contextualization, thus enabling schools to adapt the curriculum to the needs of their students. Pedagogical strategies such as project-based learning, the use of authentic materials, and technology integration increase students' motivation, engagement, and language proficiency. However, challenges such as limited teacher readiness and lack of development of teacher professional resources hinder optimal implementation. This study highlighted the importance of systemic support through training, resource allocation, and collaborative professional communities to realize complete curriculum implementation.